Corrosion mechanisms in titanium oxide-based films produced by anodic treatment. (20th April 2017) - Alves, A.C.; Wenger, F.; Ponthiaux, P.; Celis, J.-P.; Pinto, A.M.; Rocha, L.A.; Fernandes, J.C.S.
Abstract: Thanks to its excellent corrosion resistance, good mechanical properties and biocompatibility, titanium has been widely used as dental implant material. A passive oxide film formed on titanium surface is responsible for its high corrosion resistance. This study has evaluated the surface characteristics of oxide layers formed on commercially pure titanium samples by anodic treatment and the effect of anodic treatment on their corrosion behaviour. FEG-SEM and XRD were used to evaluate the micromorphology and crystalline structure of these oxide films. Their corrosion resistance was evaluated using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization curves. EIS was performed for different times of immersion and a new equivalent electrical circuit (EEC) is proposed to fit the experimental data of the anodic oxide films. It was concluded that the morphology, composition, and structure of the outer porous layer of the anodic layer determine the corrosion protection of the material.